Uwagi o globalnej polityce ekonomicznej Międzynarodowego Funduszu Walutowego - Piątkowski, Bogdan; Stelmach, Jerzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
There has been a great deal of criticism raised against the International Monetary Fund's prescription. The IMF itself came to acknowledge some of these criticisms. This paper provides a study concerning the chosen comments on global economic policy of IMF. The main aim is to present and assess views of the authorities on successes, failures, conducted reforms, and future of the organization. The notes considered in this paper are analyzed from two perspectives: economic and political. The obtained conclusions can be of help in better understanding of new directions of the Fund's activity. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 435-443